TRANSFORMATION OF POSITION AND ROLE OF THE WOMAN IN SOCIETY: PROBLEM ANALYSIS ИЗМЕНЕНИЕ ПОЛОЖЕНИЯ И РОЛИ ЖЕНЩИНЫ В ОБЩЕСТВЕ: АНАЛИЗ ПРОБЛЕМЫ ЗМІНА ПОЛОЖЕННЯ І РОЛІ ЖІНКИ У СУСПІЛЬСТВІ: АНАЛІЗ ПРОЛЕМИ - A. S. Armen (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
This article is devoted the analysis of of change the role of woman in the different spheres of society’s functioning. Reasons of such transformation are considered in this article. The problems are formulated by author that arising up as a result increases of social activity of women. Данная статья посвящена анализу процесса изменения роли женщины в различных сферах жизнедеятельности социума; рассмотрению причин такой трансформации. Автором формулируются проблемы, возникшие в результате повышения социальной активности женщин. Данна стаття присвячена аналізу процесу зміни ролі жінки у різних сферах життєдіяльності соціуму; розгляду причин подібної трансформації. Автором формулюються
проблеми, що виникли в результаті підвищення соціальної активності жінок.